Hausa Sensory Symbolism - Richie, Ian (Anthropologica, 2022)
Hausa folk tales and proverbs suggest that Hausa culture traditionally placed a high value on non-visual modes of experiencing the world, especially those of taste and smell. Concomitantly, sight is de-emphasized in comparison to Western culture. Selected items of folk lore are examined and the relative roles of the different senses compared.